2014
DOI: 10.1080/08870446.2013.871283
|View full text |Cite
|
Sign up to set email alerts
|

Shame, self-acceptance and disclosure in the lives of gay men living with HIV: An interpretative phenomenological analysis approach

Abstract: In San Francisco, a city with a great deal of acceptance surrounding HIV and a large, politically active community of persons living with HIV, gay men continue to struggle with disclosure and stigma. This stigma may be an unexpected result of a high degree of HIV testing and attempts by both HIV-positive and negative gay men to practise serosorting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…For these reasons, we have employed Interpretative Phenomenological Analysis (IPA) (19) to provide an indepth exploration of the experience of treatment in a group of women of West 7 African heritage living with HIV in London with documented difficulties with adherence to ART. Indeed, Skinta and colleagues (20) have demonstrated that IPA can be used extremely effectively to uncover the nuances and details within the lifeworlds of a small group of people living with HIV, as we aim to do in this paper. IPA is an idiographic, experiential, psychological methodology which provides a detailed analysis of convergences and divergences in individuals' accounts of their lived experience.…”
mentioning
confidence: 99%
“…For these reasons, we have employed Interpretative Phenomenological Analysis (IPA) (19) to provide an indepth exploration of the experience of treatment in a group of women of West 7 African heritage living with HIV in London with documented difficulties with adherence to ART. Indeed, Skinta and colleagues (20) have demonstrated that IPA can be used extremely effectively to uncover the nuances and details within the lifeworlds of a small group of people living with HIV, as we aim to do in this paper. IPA is an idiographic, experiential, psychological methodology which provides a detailed analysis of convergences and divergences in individuals' accounts of their lived experience.…”
mentioning
confidence: 99%
“…The participants' accounts of avoidance attests to the avoidance strategy that many gay men fearful of homophobic violence engage in (Almeida, Johnson, Corliss, Molnar and Azrael 2009;Icard et al 2015;Jacques 2014;Plant, Zielaskowski and Buck 2014;Skinta, Brandrett, Schenk, Wells and Dilley 2013). Strategies of avoidance of avowed physical spaces or social spaces where one's sexuality is considered problematic can be read as a survival strategy that enables the individual to maintain a sense of well-being, both physically and mentally.…”
Section: Survival Strategies Avoidancementioning
confidence: 98%
“…Similarly, findings from qualitative research in Thailand showed that perceived stigmatization, shame and fear of rejection were barriers towards disclosure and women in Vietnam were more likely than men to experience discrimination (e.g., denied health services) despite having laws that prohibited discrimination against individual with HIV/AIDS [52,53]. Skinta et al, conducted an interpretative phenomenological study and interviewed three HIV-positive gay men to explore their experiences of stigma and social support [54]. Findings indicated that they found difficulties initiating and establishing new relationships due to elevated levels of felt stigma and social marginalization which negatively impacted on their well-being.…”
Section: Hiv Stigmamentioning
confidence: 99%